2019
DOI: 10.1016/j.ncrna.2019.01.003
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNAs: Functional regulatory players in breast cancer

Abstract: Historically, the long-held protein-centered bias has denoted 98% of the human genome as ‘Junk’ DNA. However, the current work has shifted the perception of such 'junk' transcriptional products to functional regulatory molecules. The recent surveillance of the human transcriptome has highlighted the pivotal role of such non-coding RNA (ncRNA) molecules in diverse physiological and pathological conditions. Long non-coding RNA (lncRNA) is a recent class of ncRNA molecules that is still in its infancy stage. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 125 publications
1
66
0
Order By: Relevance
“…LncRNAs, a new kind of non-coding RNA, are longer than 200 nucleotides in length with no or limited protein-coding potential [6]. LncRNAs have been proved to play critical function in tumorigenesis through transcriptional levels to post-transcriptional levels [7,8]. lncRNAs are able to regulate the proliferation, apoptosis, migration and invasion of human cancer cells [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs, a new kind of non-coding RNA, are longer than 200 nucleotides in length with no or limited protein-coding potential [6]. LncRNAs have been proved to play critical function in tumorigenesis through transcriptional levels to post-transcriptional levels [7,8]. lncRNAs are able to regulate the proliferation, apoptosis, migration and invasion of human cancer cells [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Their dysfunction and specific role in various diseases, especially cancer, have attracted more and more attention recently. [13][14][15] LncRNAs genomic mutants or alteration have been widely clarified to induce oncogenic effect in multiple cancer types, such as breast cancer, 16 colorectal cancer, 17 ovarian cancer, 18 gastric cancer, 19 lung cancer, 20 as well as AML. 21,22 Several lncRNAs, including lnc_071255/Pvt1, lnc_104449, or lnc_177417, are found essential for AML maintenance and normal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of evidences suggest that LncRNAs are important to the regulation of cell differentiation, proliferation, and apoptosis (Tay et al 2014). It is also known that aberrant expression of LncRNAs have crucial roles in the initiation and development of various human cancers, including breast cancer (Youness and Gad 2019). In this study, we found that MT1JP expression was down-regulated in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 53%